Influência da geometria do pilar no projeto de blocos sobre duas estacas - Paulino, Cleiton Fernandes (Universidade Federal de São Carlos, 2024)
Two-pile caps are the most common elements in the transition between deep foundations and the superstructure of a building. This work presents the design of two-pile caps subjected to five different column sections. Through this analysis, the mechanical parameters that govern the behavior of a rigid two-pile cap were evaluated, in order to understand the influence of the column geometry on the foundation element. For this purpose, input parameters and two combinations of loading conditions acting on the column were predefined, in addition to conditions of the distance at which the effort reactions will be transmitted to the piles, which affects the inclination and angle of the concrete struts. The analysis of the influence of the column geometry on the design of two-pile caps was carried out through tables and graphs. All models were designed and dimensioned according to Brazilian normative recommendations. It is expected that this work will find limits between the geometry of the rectangular column and the distance and arrangement of the piles in a two-pile cap and contribute to the design of this structural element.
Influence of column geometry on two pile-caps
Keywords: Bloco sobre estacas; Concreto armado; Blocos rígidos; Geometria do pilar; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS